Teachers' Perception of the Ethical Use of Artificial Intelligence in their Educational Work (Innovaciones Educativas, 2024)
The main objective of the article is to analyze the perception of Costa Rican teachers regarding the ethical use of Artificial Intelligence (AI) in their educational work. The paper deals with AI in education, its definition, characteristics and how it is perceived by Costa Rican teachers at the elementary, high school and university levels. It also discusses the ethical considerations regarding its use for educational purposes and the diversity of AI tools, their application and the experiences that teachers have had with them. The research was conducted using a concurrent mixed methods approach and relied on descriptive analysis techniques. For data collection, 134 teachers from all educational backgrounds in Costa Rica responded to a questionnaire. The data were analyzed using qualitative and quantitative strategies. The results show that teachers have limited knowledge about the use of Artificial Intelligence for educational purposes. Also, although some of them consider that AI could be useful to support students, they are not aware of the possibilities that AI offers to adapt content for individualized learning. The article concludes that teachers are aware of the importance of the AI approach and the ethical implications of using it in the classroom. Finally, there is a need for better training on how to best use AI tools.
Keywords: Learning; Education; Teacher Innovation; Emerging Technologies; Artificial Intelligence